Low‐fasting triglyceride levels are associated with non‐invasive markers of advanced liver fibrosis among adults in the United States. Issue 1 (27th April 2015) - Jiang, Z. G.; Tsugawa, Y.; Tapper, E. B.; Lai, M.; Afdhal, N.; Robson, S. C.; Mukamal, K. J.
Summary Background Elevated fasting triglyceride is often associated with metabolic syndrome and non‐alcoholic fatty liver disease (NAFLD), the most common form of chronic liver disease. On the other hand, as liver disease progresses, patients may develop hepatocellular dysfunction that impairs triglyceride production. Aim To test the hypothesis that lower fasting triglyceride levels may paradoxically indicate more advanced liver disease. Methods A cross‐sectional analysis of 11 947 adults aged 20 years or older without chronic viral hepatitis from the National Health and Nutrition Examination Survey 1999–2010 was performed to analyze the relationships between fasting triglyceride levels and five validated non‐invasive indices of liver fibrosis, including Fibrosis 4 Score (FIB4), NAFLD Fibrosis Score (NFS), Ast‐Platelet Ration Index, AST/ALT ratio and BARD. Results Low‐fasting triglyceride levels were consistently associated with elevated liver fibrosis indices. Individuals in the lowest quintile of triglycerides (TG) had an adjusted odds ratio (OR) of 3.0 (95% CI, 1.7–5.2; P < 0.001) for advanced fibrosis estimated by FIB4 score and OR of 1.8 (95% Cl, 1.2–2.7; P = 0.009) estimated by NFS, compared to individuals in the highest quintile. This association remained highly significant when restricted to individuals with abnormal LFTs from suspected NAFLD. This inverse relationship was continuous, and more pronounced among men and whites (P interaction <0.001 and 0.008 respectively), but not modified by age or body mass index. In addition, fasting TG had a stronger, more direct association with liver fibrosis indices than did albumin or total bilirubin. Conclusions Fasting triglyceride levels were inversely associated with liver fibrosis indicators in American adults, especially among white men. Our findings suggest that sequential lipid measurements may serve as a useful disease marker in the management of chronic liver disease patients.